Multimedia Interaktif Sebagai Media Visualisasi Perakitan Komputer - Wahyudiani, Evi; Rasyid, Harun; Saputra, Hendra Nelva (Universitas Lampung, 2020)
This research was based on complex process in implementing computer assembly with the limitation of facilities that cause the low concept mastery and not growing critical thinking skills of students. The purpose of this research was to facilitate the mastery of concepts and improvement of students' critical thinking skills by utilizing visualization techniques in interactive multimedia. The research method used in this study was Lee and Owens (2004) development model consisting of 4 steps namely analysis, design, implementation and development, and evaluation. The development product produced was an interactive multimedia. The results of an interactive multimedia feasibility based on the assessment of the media experts, subject matter experts, and the students received a level of validity of 84.4% from the media expert, 83% from content expert, and 81.6% from students with the interpretation of worthy of use. The concept mastery of students based on the pretests gets an average value of 51.7 and gets an average value of 82.3 at post-test. The comparative assessment of critical thinking skills gained from pretests and posttest responses has always shown an increase in each indicator. The results of this study proved that interactive multimedia is effectively used in learning.Keywords: Interactive Multimedia, Concept Mastery, Critical Thinking Skills, Computer AssemblyDOI : http://dx.doi.org/10.23960/jpvti.v2.i1.202005.